Social Disclosure's Ascendancy in Energy Corporate Valuation: Outpacing Economic, Environmental, and Governance Dimensions - Hernisa Hernisa; Alfonsa Dian Sumarna (Politeknik Ganesha Medan, 2026)
A sustainability report is a key tool for corporate accountability, communicating a company’s performance and value to stakeholders. This study investigates the role of such reports, specifically examining how their economic and ESG (Environmental, Social, and Governance) disclosures influence company value. This study extends previous ESG research by isolating the social dimension as the primary driver of firm value in Indonesia’s energy sector. The research utilized data from energy sector companies listed on the Indonesia Stock Exchange from 2021 to 2023. A purposive sampling method was used, yielding 102 observational samples. The data were analyzed using multiple linear regression in EViews 12 to test the associations. The analysis revealed that economic, environmental, and governance disclosures individually do not have a significant effect on company value. In contrast, social disclosure was found to exert a significant positive influence. Furthermore, the simultaneous effect of all ESG and economic dimensions was significant. This indicates that while social factors are individually critical, the integrated reporting of all dimensions jointly impacts value. For energy companies facing significant social challenges, disclosing social performance is crucial. It not only strengthens legitimacy but also directly enhances market value by improving reputation, fostering consumer loyalty, and building stronger community relations.